The ID Dominance in Kathleen Glasgow’s Novel Girl in Pieces (2016) - Madiar, Melati Vaya Nugraha; Marlina, Leni (Universitas Negeri Padang, 2024)
Nowadays, it is important to provide a deeper understanding of the psychological dynamics underlying self-injurious behavior in the context of fictional narratives, so that it can provide new insights into our understanding of mental health problems and the prevention of such dangerous behavior. This study aims to examine how the id dominance of the character Charlie in Kathleen Glasgow's novel